2016
DOI: 10.12776/qip.v20i2.744
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Appreciative Inquiry, Lean and Perceived Co-worker Health

Abstract: Purpose: The purpose of this paper is to present a developed questionnaire which measure Appreciative Inquiry, Lean values and co-workers health. The purpose is also to explore if and how Appreciative Inquiry correlates with Lean values and co-workers' perceived health in an organisation working with Lean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…The developed main areas, factors and statements about team collaboration within and between hospital units were included in an existing questionnaire assessing quality culture. The earlier questionnaire was used and tested in different settings and contexts (see, for instance, Bäckström and Ingelsson, 2016). This original questionnaire consisted of 36 statements representing 12 different factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed main areas, factors and statements about team collaboration within and between hospital units were included in an existing questionnaire assessing quality culture. The earlier questionnaire was used and tested in different settings and contexts (see, for instance, Bäckström and Ingelsson, 2016). This original questionnaire consisted of 36 statements representing 12 different factors.…”
Section: Methodsmentioning
confidence: 99%
“…The earlier questionnaire was used and tested in different settings and contexts (see, for instance, Bäckström and Ingelsson, 2016). This original questionnaire consisted of 36 statements representing 12 different factors.…”
Section: Development Of a Questionnairementioning
confidence: 99%
“…Value-based leadership "Appreciative Inquiry," "Pride," "Health" and "Continuous improvements" (Lagrosen et al, 2012;Bäckström, Eriksson and Lagrosen, 2012;Bäckström, Ingelsson and Wiklund, 2012;Bäckström et al, 2014;Ingelsson, 2013;Ingelsson and Mårtensson, 2014;Bäckström and Ingelsson, 2015).…”
mentioning
confidence: 99%
“…A leadership inspired by AI has also led to positive effects on the working environment and decreased sick leave (Åslund et al , 2011). Bäckström and Ingelsson (2015) found that AI may help organizations to work in a structured and conscious way to reduce sick leave after studying if and how AI correlates with Lean values and co-workers’ perceived health when studying a Swedish municipality.…”
Section: Values Within Quality Managementmentioning
confidence: 99%
“…The purpose of the survey was to measure soft values, to obtain an overview of the culture within the organizations and to investigate if the activities had influenced the culture and the leadership. Based on three previously tested surveys, a new survey was compiled to measure the co-workers and the leaders’ perception of the factors: “committed leadership” (consisting of the three dimensions: empathy, presence and communication and integrity), “participation of everybody” (consisting of the three dimensions: development, influence and being informed) and “customer focus”, “system view”, “continuous improvements,” “AI”, “pride” and “health.” The earlier questionnaires had been tested and used in many different organizations to evaluate different quality development and improvement projects in those organizations (Lagrosen et al , 2012; Bäckström et al , 2012a; Bäckström et al , 2012b; Bäckström et al , 2014; Ingelsson et al , 2010; Ingelsson, 2013; Ingelsson and Mårtensson, 2014; Bäckström and Ingelsson, 2015; Ingelsson and Bäckström, 2017). The new survey was used in two of the companies twice during the project time.…”
Section: The Project and Accomplished Activitiesmentioning
confidence: 99%